2011
DOI: 10.3126/jnps.v31i2.4094
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial <i>Citrobacter</i> Infection in Neonatal Intensive Care Unit in a Hospital of Nepal

Abstract: Introduction: Neonatal Citrobacter infection is either acquired horizontally or vertically as a nosocomial infection. The source of nosocomial Citrobacter is either hands of medical staff or the innate objects. Objective: The aim of this study was to study nosocomial Citrobacter infection in neonates admitted in Neonatal Intensive Care Unit (NICU) and trace the source of infection. Methods: The study was conducted in NICU in a hospital in Kathmandu, Nepal during a period of January to March 2010. Specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This finding is important as it points to one of the significant vectors for transmission of this emerging neonatal pathogen. The fact that the isolates showed a multi-drug resistant pattern is in agreement with a study by Khadka et al [32]. In that study, the sensitivity of Citrobacter species to floroquinolones was shown to be higher, which is in agreement with our findings of good sensitivity for Norfloxacin and Ciprofloxacin.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is important as it points to one of the significant vectors for transmission of this emerging neonatal pathogen. The fact that the isolates showed a multi-drug resistant pattern is in agreement with a study by Khadka et al [32]. In that study, the sensitivity of Citrobacter species to floroquinolones was shown to be higher, which is in agreement with our findings of good sensitivity for Norfloxacin and Ciprofloxacin.…”
Section: Discussionsupporting
confidence: 94%
“…Citrobacter spp. were implicated as causes of neonatal nosocomial infections in a randomized population‐based study in Nepal (Khadka et al ., ). Recently, a study conducted in a neonatal intensive care unit in Ethiopia showed Citrobacter to be the second most common isolate from cockroaches, thereby suggesting its relevance as an emerging multidrug‐resistant neonatal pathogen (Tilahun et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…infection is prevalent in Nepal, it is unfortunate that no systematic molecular studies have been conducted, however the isolation of Citrobacter spp. have been described 2,8,9 . In this study, we have shown the emergence of C. freundii carrying class 1 integron element and bla CTX-M and bla TEM-1 ESBL genes for the fi rst time in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…are most common 1 . Citrobacter nosocomial infection in neonates is a cause of substantial rise in morbidity and mortality of neonates in the hospital in Nepal and globally 1,2,3,4 . The poor infection prevention and control practices have been a major determining factor for the spread of this nosocomial pathogen 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation